Object oriented programming with QuickPascal - Shammas, Namir Clement (New York : Wiley, 1990)
A state-of-the-art guide to the powerful features of QuickPascal, including object-oriented programming, the built-in debugger, and compatibility with Borland's Turbo Pascal. Explains all language updates, from data declarations to error handling, offers a complete overview of the code development environment, and includes techniques for quickly translating routines from Turbo Pascal and standard Pascal into QuickPascal. Includes many helpful examples of actual code using QuickPascal's special object-oriented characteristics.